THE VALUATION OF THE BLACK: a look at afro-entrepreneurship in São Carlos/SP - Nascimento, Rafaela Helena do; Colenci Trevelin, Ana Teresa (Revista Interface Tecnológica, 2021)
Since the slave-owning period, with the approval of their masters, the black population performed activities, in addition to harvesting, activities that generated extra income, such as artisanal and homemade services, as one of the countless forms of survival and an attempt at emancipation. Over time, such activities came to be seen by the black population as a strategy to face economic and social vulnerability, in such a way that nowadays, blacks have become owners of their own businesses, in their micro and small companies. Thus, the term Afro-entrepreneurship emerges, a form of identification and current ideology for the strengthening and maintenance of black identity among entrepreneurs. The present article had as proposal to carry out a bibliographic survey about the emergence of the term afroentrepreneurship in the current society and to analyze the trajectory of black entrepreneurs in the city of São Carlos, aiming with the use of the descriptive qualitative methodology to understand the experiences pervaded by the paths of black entrepreneurs from the city, leading to a reflection on the still present problems caused by the slave-owning period in the lives of black entrepreneurs to the present day and the relationship and identification of the black population with the term afro-entrepreneurship. Based on the data collected, it is intended to develop a Business Training Program for Afro-entrepreneurs.